Ex vivo perfusion model of mouse liver and its application to analyze the effects of OCT1 deficiency - Rönnpagel, Vincent; Morof, Felix; Ciarimboli, Giuliano; Grube, Markus; Meyer-Tönnies, Marleen J.; Tzvetkov, Mladen V. (Frontiers in Pharmacology, 2025)
IntroductionThe liver plays a critical role in drug pharmacokinetics. In in vivo experiments, it is difficult to isolate the liver’s contribution to drug systemic concentrations from that of the intestine and kidneys. Rat liver perfusion is well-established for studying liver-specific effects. However, rats are not easily genetically manipulated, complicating analyses of individual drug transporters and metabolizing enzymes. This study aimed to establish an ex vivo liver perfusion model in mice and to apply it to analyze the effects of mOct1 on drug metabolism.MethodsAfter euthanizing, the liver of 6- to 28-week-old mice was perfused via an indwelling venous catheter in the portal vein as entry and into the caudal vena cava toward the heart as exit. Perfusion solutions were prewarmed to 42 °C and pumped at 2 mL/min. First, HBSS supplemented with 0.5 mM EDTA was used to exsanguinate the liver, followed by HBSS alone and then HBSS containing the drug of interest. Drug and metabolite concentrations in the perfusates were measured by LC-MS/MS.Results and conclusionThe method enables reproducible and reliable perfusion of mouse livers. We applied it to study the effects of Oct1 knockout on drug metabolism. Oct1 knockout affected the first-pass metabolism of codeine, including the formation of the metabolites morphine and morphine-3-glucuronide, as well as the first-pass metabolism of proguanil and the formation of cycloguanil. The model is applicable to any mouse strain, genetic background, and substrate of interest and is thus applicable to a wide variety of research questions.